Effects of Precursor Structure on First-Generation Photo-Oxidation Organic Aerosol Formation - Sofio, D.; Long, D.; Kohls, T.; Kunz, J.; Wentzel, M.; Hanson, D. (Frontiers in Environmental Science, 2022)
The effect of precursor molecular structural features on secondary organic aerosol (SOA) growth was investigated for a number of precursor functional groups. SOA yields were determined for straight chain alkanes, some oxygenated, up to highly functionalized hydrocarbons, the largest being β-caryophyllene. Organic SOA yield was determined by comparing to standard particle size changes with SO2 in a photolytic flow reactor. SOA formation was initiated with OH radicals from HONO photolysis and continued with NO and NO2 present at single-digit nmol/mol levels. Seed particles of ∼10 nm diameter grew by condensation of SOA material and growth was monitored with a nanoparticle sizing system. Cyclic compounds dominate as the highest SOA yielding structural feature, followed by C-10 species with double bonds, with linear alkanes and isoprene most ineffective. Carbonyls led to significant increases in growth compared to the alkanes while alcohols, triple-bond compounds, aromatics, and epoxides were only slightly more effective than alkanes at producing SOA. When more than one double bond is present, or a double bond is present with another functional group as seen with 1, 2-epoxydec-9-ene, SOA yield is notably increased. Placement of the double bond is important as well with β-pinene having an SOA yield approximately 5 times that of α-pinene. In our photolytic flow reactor, first-generation oxidation products are presumed to be the primary species contributing to SOA thus the molecular structure of the precursor is determinant. We also conducted proton-transfer mass spectrometry measurements of α-pinene photooxidation and significant signals were observed at masses for multifunctional nitrates and possibly peroxy radicals. The mass spectrometer measurements were also used to estimate a HONO photolysis rate.